النقد المعرفي والتشكيل الإدراكي للغة - قدري, رانية; عروس, محمد (جامعة الوادي - University of Eloued, 2021)
تسعى هذه الدراسة إلى الكشف عن التحول الذي أحدثته الثورة الإدراكية في عملية اشتغال المعارف من منظور اللغة، وكذا التعرف على النقد المعرفي الذي جسد حضورا قويا في سيرورة اشتغاله النقدي، أولا في شموليته للمعارف، وثانيا في تغييره لمسار اللغة من الشعري إلى المعرفي. وتهدف إلى الإجابة عن الإشكالية الآتية: كيف تجسد التشكيل الإدراكي للغة في النقد المعرفي؟ وما أهمية هذا الاشتغال؟ وكيف تحول مسار اللغة مع الثورة الإدراكية؟ معتمدين في ذلك المنهج الوصفي باستخدام التحليل والتركيب كآليات إجرائية تمكننا من وصف القضايا المطروحة ومعالجتها This study seeks to uncover the transformation brought about by the perceptual revolution in the process of knowledge functioning from the perspective of language, as well as to identify the cognitive criticism that embodied a strong presence in the process of its critical work, first in its comprehensiveness of knowledge, and secondly in its change of the course of language from poetic to epistemic. It aims to answer the following problem: How do you embody the perceptual formation of language in cognitive criticism? What is the significance of this work? And how did the course of language change with the cognitive revolution? They adopted the descriptive approach using analysis and synthesis as procedural mechanisms that enable us to describe and address the issues raised.
مقال
Keywords: النقد المعرفي ; اللغة ; اللسانيات المعرفية ; الاستعارة المعرفية; Cognitive criticism ; The language ; Cognitive Linguistics ; The cognitive metaphor